STUDI PENANGGULANGAN BANJIR KALI KETING KABUPATEN JEMBER - Abdul Rahman, Muhammad; Saud, Ismail; Aziz, S. Kamilia (Universitas Negeri Malang, 2023)
Kali Keting is a river located in Jember Regency, East Java Province. The land use of the Keting River Watershed (DAS) is predominantly villages and rice fields. Some of the rice fields are in the middle and upstream of the Kali Keting watershed. On the upstream side, when there is a large discharge, overflow occurs. In fact, the overflow occurred for 5 days and inundated people's houses to a depth of 50 - 60 cm. And in the rice fields, flooding also occurred which inundated 157 ha of rice crops and 26.33 ha of sugar cane crops. So it is necessary to carry out studies for flood prevention. The methods used are the calculation of the planned pearson type 3 log rain analysis, the planned flood discharge calculation using the Nakayasu unit hydrograph method, hydraulic modeling using HEC-RAS software for existing and planned conditions, and discussion of the results of the hydraulic analysis. From the results of the analysis, it was found that action was needed in the form of river normalization. In critical gutters, reinforcement with lining is required.